Preparation by alkaline treatment and detailed characterisation of empty hepatitis B virus core particles for vaccine and gene therapy applications - Strods, Arnis; Ose, Velta; Bogans, Janis; Cielens, Indulis; Kalnins, Gints; Radovica, Ilze; Kazaks, Andris; Pumpens, Paul; Renhofa, Regina (Scientific reports, 2015)
Hepatitis B virus (HBV) core (HBc) virus-like particles (VLPs) are one of the most powerful protein engineering tools utilised to expose immunological epitopes and/or cell-targeting signals and for the packaging of genetic material and immune stimulatory sequences. Although HBc VLPs and their numerous derivatives are produced in highly efficient bacterial and yeast expression systems, the existing purification and packaging protocols are not sufficiently optimised and standardised. Here, a simple alkaline treatment method was employed for the complete removal of internal RNA from bacteria- and yeast-produced HBc VLPs and for the conversion of these VLPs into empty particles, without any damage to the VLP structure. The empty HBc VLPs were able to effectively package the added DNA and RNA sequences. Furthermore, the alkaline hydrolysis technology appeared efficient for the purification and packaging of four different HBc variants carrying lysine residues on the HBc VLP spikes. Utilising the introduced lysine residues and the intrinsic aspartic and glutamic acid residues exposed on the tips of the HBc spikes for chemical coupling of the chosen peptide and/or nucleic acid sequences ensured a standard and easy protocol for the further development of versatile HBc VLP-based vaccine and gene therapy applications.